Comprehensive effects of fecal microbiota transplantation on cynomolgus macaques across various fecal conditions - Kang, Philyong; Bae, Gyu-Seo; Jeon, Eunsu; Choi, Jeonghwa; Hwang, Eun-Ha; Kim, Green; Baek, Seung Ho; Shim, Kyuyoung; An, You Jung; Lim, Kyung Seob; Kim, Yujin; Oh, Taehwan; et al. (Frontiers in Microbiology, 2024)
Fecal microbiota transplantation (FMT) and probiotics therapies represent key clinical options, yet their complex effects on the host are not fully understood. We evaluated the comprehensive effects of FMT using diarrheal or normal feces, as well as probiotic therapies, on multiple anatomical sites in healthy cynomolgus macaques through colonoscopy and surgery. Our research revealed that FMT led to a partial microbiome transplantation without exhibiting the donor’s fecal clinical characteristics. Notably, FMT increased insulin and C-peptide levels in each animal according time series, regardless of fecal conditions. Immunologically, a reduction in neutrophil-to-lymphocyte ratio were exclusively observed in femoral veins of FMT group. In blood chemistry analyses, reductions in aspartate aminotransferase, blood urea nitrogen, and creatinine were observed in the femoral veins, while elevated levels of alanine aminotransferase and calcium were exclusively detected in the portal veins. These changes were not observed in the probiotic group. Also, short chain fatty acids were significantly higher increase in portal veins rather than femoral veins. Transcriptome analysis of liver tissues showed that metabolic pathways were primarily affected by both FMT and probiotics therapies. In summary, FMT therapy significantly influenced metabolic, immunologic and transcriptomic responses in normal macaque models, regardless of fecal conditions. Also, these macaque models, which utilize surgery and colonoscopy, serve as a human-like preclinical platform for evaluating long-term effects and anatomically specific responses to gut-targeted interventions, without the need for animal sacrifice.